PERSEPSI DAN POLA KONSUMSI REMAJA SELAMA PANDEMI COVID-19 - Wiwin Efrizal (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2020)
Covid-19 has an impact on adolescents, both directly in the form of exposure to the virus and in the form of secondary effects caused by efforts to stop transmission. Adolescence is a transitional period where critical thinking begins, but is sometimes controlled by an unstable emotional state. Changes in conditions caused by the Covid-19 pandemic can affect the psychosocial and consumption patterns of adolescents. This study aims to determine adolescents' perceptions of Covid-19 and their consumption patterns during the pandemic. This is a cross-sectional study with a sample of 95 adolescents who were sent randomly linked questionnaires during the first week of September 2020. Data analysis was carried out using descriptive statistics and graphs. Teens who were not sure and doubted the covid-19 virus were 14.7% and considered it a conspiracy, because there was no clear evidence and information. Changes in consumption patterns were felt by 37.9% of adolescents during a pandemic. Adaptation to new habits that was most difficult for adolescents was to avoid crowding and only 38.7% could do it. A small proportion of teenagers are unsure or doubt the existence of the Covid-19 virus, due to lack of clear information. The pandemic causes stress for teenagers and has an impact on changing consumption patterns. The adoption of new habitual adaptations has not been fully carried out, even though most teenagers are convinced of the Covid-19 virus. The need for clear information about the covid-19 virus and strengthening the application of health protocols in adolescents.